Funny or Angry? Neural Correlates of Individual Differences in Aggressive Humor Processing - Liu, Xiaoping; Chen, Yueti; Ge, Jianqiao; Mao, Lihua (Frontiers in Psychology, 2019)
Humor is a hot topic for social cognition in recent years. The present study focused on the social attribute of humor and showed different stories to participants, which were divided into four types according to the model of humor style, to explore the underlying neural mechanism of point-to-self aggressive humor and how individual differences modulated it. Measuring the degree of anger and funniness, results suggested that aggressive humor helped us in social communication by reducing the degree of anger. The neural activities showed that bilateral temporal lobes and frontal lobes played a synergistic role in the point-to-self aggressive humor processing, while point-to-self non-aggressive humor was dominant in the left-side brain. Results from the region of interest (ROI) analysis showed that the individual differences of the self-control level and the self-construal level may influence the neural processing of point-to-self aggressive humor by modulating the activated levels and patterns of the right inferior orbital frontal gyrus, the right superior temporal lobe and the right superior frontal lobe.